Survey af occurrence of the pineapple mealybug Dysmicoccus brevipes in two regions of production in the state of Minas Gerais, Brazil - Santa Cecília, Lenira Viana Costa (2014)
This work was carried out in order to obtain information about the pineapple mealybug Dysmicoccus brevipes in two regions of pineapple production in the state of Minas Gerais, Brazil. Sampling at ten properties (cv Pérola) in Piui confirmed the presence of this insect at low infestation levels. In Monte Alegre de Minas, six out of ten properties sampled (cv Cayenne) showed low infestations levels while the other four properties had average infestations in accordance with the Class of Infestation elaborated by Vilardebo & Guérout (1966).